The Effect of Yoga Exercises on Sleep Quality for The Elderly - Mala Rispa; Ira Kusuawaty; Siti Hindun (Poltekkes Kemenkes Palembang, 2021)
Background: : Sleep disturbances are common in the elderly. As a person ages, the less sleep duration is needed, this is due to a decrease in the function of cells and organs in the body. Yoga practice is one of the non-pharmacological therapeutic methods that can be applied in overcoming poor sleep quality in the elderly Purpose: To determine the effect of Yoga Practice on Sleep Quality for the Elderly at the Panti Social Tresna Werdha Teratai , Palembang City in 2021 Methods: This study is a quantitative study using the Pre Experiement Design research method and the One Group pretest-posttest design model. Sampling Techniques Using Total Sampling included in the inclusion criteria that have been determined by the researchers, as many as 31 respondents. Data were analyzed using Mc.Nemar statistical test. Results: Through bivariate analysis using Mc.Nemar's test on the sleep quality of respondents before and after yoga practice was given to show that the significance value of p was 0.000 (p ≤ 0.05), which means that there is a difference between the sleep quality of respondents before and after the intervention. Conclusion: There is an effect of yoga practice on the sleep quality of the elderly. To overcome poor sleep quality in the elderly, it is expected that the elderly and nursing home administrators apply yoga as a non-pharmacological method in overcoming sleep disorders or poor sleep quality.